Treatment of Textile Wastewater with Activated Carbon Produced from Plum Seed Shell - Mon Yi Myo Myint; Zin Marlar Tin San; Nway Nway Khaing (AI Society & STMIK Indonesia, 2026)
In this study, the activated carbon derives from plum seed shells are used for the treatment of textile wastewater collected from the Wandwin area which has high concentrations of parameters such as pH, colour, TSS, TDS, COD, and BOD. pH value of textile wastewater is 12.4 that leads to alkaline, so pH adjusts with alum coagulants. After treatment the COD concentration can be reduced from 1280 mg/l to 20 mg/l by using equilibrium concentration of activated carbon, Ce =50 mg/. The adsorption data followed the Langmuir isotherm (R² = 0. 0.97832). Other parameters also significantly decreased from 74.74 % to 98.29%. According to the National Enviromental Quality Guideline (NEQG) Myanmar, all treated water parameters comply with NEQG standards. Therefore, the plum seed shell activated carbon is an effective and sustainable material for the treatment of textile wastewater and treated effluent can be safely discharged into the surrounding water bodies.